Cyberfaith: The Interplay of Information Technologies and Muslim Youth in Shaping Contemporary Islamic Discourses - Ansor; Nasution, Awal Kurnia Putra; Husein, Muhammad (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
This study explores Cyberfaith, examining the intricate relationship between information technology and the religious perspectives of Muslim youth. With an emphasis on how the digital age has altered religious activities, the study offers complex insights into how information technology affects the spiritual perspectives of the next generation. The study adds to our understanding of the benefits and difficulties of incorporating technology into religious expressions by exploring the Cyberfaith phenomena. The findings emphasize the complexity of this influence and the part that religious beliefs play in influencing attitudes and actions. The development of Islamic religious narratives is greatly influenced by information technology, which questions established conventions and reframes concepts of authority and religion. The study's global reach demonstrates how Islamic expressions and societal elements are impacted in different parts of the world. Worship has changed as a result of the use of technology into religious rituals; this presents both opportunities and difficulties that need more investigation. The study highlights the significant change in Muslim youth's religious engagement in the digital age and stresses the significance of comprehending the effects on society and academia. Future studies should look at the implications for policy and education in helping Muslim teenagers utilize technology responsibly in religious contexts.